1998
DOI: 10.1523/jneurosci.18-16-06279.1998
|View full text |Cite
|
Sign up to set email alerts
|

Brain Endothelial Cells Express Cyclooxygenase-2 during Lipopolysaccharide-Induced Fever: Light and Electron Microscopic Immunocytochemical Studies

Abstract: Cyclooxygenase-2 (COX-2), a key enzyme in the biosynthesis of prostaglandins, is induced in brain blood vessels by pyrogens, and its essential role in fever has been hypothesized. In this study, we determined (1) the type of cells that express cyclooxygenase-2 in brain blood vessels of lipopolysaccharide-treated rats, and (2) the precise relationship between the time course of fever and that of cyclooxygenase-2 protein expression in these cells. Five hours after the lipopolysaccharide injection (100 microg/kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
137
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(154 citation statements)
references
References 32 publications
16
137
0
1
Order By: Relevance
“…We and others have reported COX-2 mRNA expression exclusively within the cerebral endothelium in models of LPS, IL-1b or sterile systemic inflammation. 4,[11][12][13][14][15][16][17]20,21,23 In addition, colocalization of both mPGES-1 and COX-2 enzymes within brain endothelial cells was also observed, 18,36 and such results have yet to be reported in perivascular cells. Finally, COX-2 induction was localized to both endothelial and perivascular microglia in response to low doses of i.p.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We and others have reported COX-2 mRNA expression exclusively within the cerebral endothelium in models of LPS, IL-1b or sterile systemic inflammation. 4,[11][12][13][14][15][16][17]20,21,23 In addition, colocalization of both mPGES-1 and COX-2 enzymes within brain endothelial cells was also observed, 18,36 and such results have yet to be reported in perivascular cells. Finally, COX-2 induction was localized to both endothelial and perivascular microglia in response to low doses of i.p.…”
Section: Discussionmentioning
confidence: 93%
“…10 Although COX-2 and mPGES-1 transcriptional activation takes place in cells of the BBB in various models of systemic inflammation, 4,11 the main cell type expressing these transcripts and producing PGE 2 is still under debate. Indeed, whereas numerous studies have provided evidence that both COX-2 and mPGES-1 transcripts and proteins are upregulated within the endothelium of the cerebral capillaries and venules, [12][13][14][15][16][17][18][19][20][21][22][23] other well-performed studies have shown that perivascular cells of hematopoietic origins play a key role in PGE 2 delivery in response to systemic inflammatory stimuli. [24][25][26] Finally, recent findings suggest that stimulation of both types of cells is required to activate the HPA axis during endotoxemia 27 and either types could mediate different phases of CNS activation.…”
Section: Introductionmentioning
confidence: 99%
“…After LPS administration, it has previously been found that COX-2 mRNA and protein are induced within the central nervous system (CNS), predominantly in vascular endothelium, but also in specific neuronal populations (4,24) as well as peripheral tissues (9,11,22,26). Prominent induction of COX-2 mRNA has been noted specifically within the parenchyma of the hypothalamic paraventricular nucleus (15).…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 is considered as a major pyrogenic mediator of fever (Engstrom et al, 2012;Matsumura et al, 1998;Yamagata et al, 2001). The role of PGE 2 in induction of fever in mammals was already reported in 1971 by Milton and Wendlandt (1971) who demonstrated that microinjection of PGE 2 into the third ventricle of conscious cats and rabbits cause a rise of body temperature.…”
Section: The Key Role Of Pgementioning
confidence: 93%